2015
DOI: 10.1080/02705060.2014.999360
|View full text |Cite
|
Sign up to set email alerts
|

A coupled modeling approach to predict water quality in Lake Taihu, China: linkage to climate change projections

Abstract: Climate change is expected to impact water quality and ecosystem health in water bodies. In this study, a modeling framework was developed to assess the response of environmental variables to climate change scenarios in Lake Taihu, China. A coupled hydrodynamic-water quality-sediment flux model was employed to simulate water quality processes under future climate scenarios projected from a general circulation model (GCM) forced by the Representative Concentration Pathway 8.5 (RCP 8.5). The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Similarly, the impact of climate change on the DO concentration in the tropical rivers shows that DO concentrations declined in the tropical rivers in parallel with water temperature increase and a similar relationship has been discussed by others [15,56]. It was observed that the water temperature and DO concentration along the river section varied independently of climate variability.…”
Section: Discussionmentioning
confidence: 51%
“…Similarly, the impact of climate change on the DO concentration in the tropical rivers shows that DO concentrations declined in the tropical rivers in parallel with water temperature increase and a similar relationship has been discussed by others [15,56]. It was observed that the water temperature and DO concentration along the river section varied independently of climate variability.…”
Section: Discussionmentioning
confidence: 51%
“…The detailed mass conservation equations for each state variable are documented in Craig (2011), Hamrick (1992) and Tetra Tech (2007). A detailed model setup, calibration and validation process with respect to hydrodynamics and water quality variables in Lake Taihu can be found in the supplementary material (Li et al, 2011b;Tang et al, 2015). The previous results showed that the model reproduced the main features of wind-driven circulation, water level and water quality state variables quite well.…”
Section: Model Setupmentioning
confidence: 58%
“…The benthic flux rates (i.e., PO 4 3− , NH4 + , NO 2 − -NO 3 − and SOD) in different lake regions were set according to the previous field experiments in Lake Taihu (Hu et al, 2006; Jiang et al, 2008;Luo et al, 2006;Tang et al, 2015;Trolle et al, 2009). The results clearly indicated that external nutrient reduction is critical to help mitigate eutrophic status but the amount of reduction needed to achieve the goal seems much higher than modeled in this study.…”
Section: System Response To Nutrient Reductionmentioning
confidence: 86%
See 1 more Smart Citation
“…; Tang et al. ). Climate scientists report with high confidence that the U.S. will experience a significant increase in the number of hot days by the end of the 21st Century (Gleason et al.…”
Section: Introductionmentioning
confidence: 99%